Measurement of Optical Scattering Coefficient of the Individual Layers of the Human Urinary Bladder Using Optical Coherence Tomography. (16th February 2014) - Ejofodomi, O'tega
Abstract : The author reports measurement of the optical attenuation of the urinary bladder using Optical Coherence Tomography. This method uses the exponential relationship that exists between the intensity of the back-scattered infrared light and the penetration depth. The method is applied to Optical Coherence Tomography images of the human urinary bladder and the scattering coefficients of the top three layers (urothelium, lamina propria, and muscle layers, resp.) are extracted. An optical attenuation ratio of 1 : 6.2 : 4.2 for the three layers is reported.